Pengaruh Online Customer Review, Online Customer Rating dan Kualitas Website Terhadap Minat Beli Secara Online - Divan Diwangga, Dimas Bagus; Ahmadi, Mirzam Arqy (Universitas Serambi Mekkah, 2024)
The rapid development of information technology has significantly changed the way consumers shop. Electronic commerce has currently become one of the most important channels to satisfy the demand for goods and services. Customer ratings or online customer reviews are a factor that plays an important role in purchasing decisions. These reviews provide consumers with information about other people's experiences with a particular product or service. In addition, the rating system or online customer opinions also influence consumers' perception of the products they want to buy. High reviews tend to increase consumer trust, while low reviews can negatively influence purchase intentions. In addition to this, the quality of the website used for purchases is no less important. An easily accessible, attractive, and user-friendly website can increase visitor convenience, which in turn can influence purchasing decisions.The purpose of this research is to study and evaluate whether there is an influence between online customer reviews, online customer ratings, and website quality on interest in online shopping. This research uses a quantitative methodological approach. The sample used in this research was made up of 53 respondents residing in Surakarta and with experience in online shopping. This research sample was drawn using a non-probability sampling technique such as convenience sampling. The partial least squares (PLS) method was applied to data analysis using SmartPLS 3.0 software. The research results show that online customer rating (X1), online customer rating (X2) and website quality (X3) have a positive and significant influence on online purchasing interest. (Y) in electronic commerce.